Construction of Infrared‐Light‐Responsive Photoinduced Carriers Driver for Enhanced Photocatalytic Hydrogen Evolution. Issue 12 (11th February 2020) - Dai, Baoying; Fang, Jiaojiao; Yu, Yunru; Sun, Menglong; Huang, Hengming; Lu, Chunhua; Kou, Jiahui; Zhao, Yuanjin; Xu, Zhongzi
Abstract: Infrared light, more than 50% of the solar light energy, is long‐termly ignored in the photocatalysis field due to its low photon energy. Herein, infrared‐light‐responsive photoinduced carriers driver is first constructed taking advantage of pyroelectric effect for enhancing photocatalytic hydrogen evolution. In order to give full play to its role, the photocatalytic reaction is localized on the surface and interface of the composite based on a new semi‐immersion type heat collected photocatalytic microfiber system. The system is consisted of distinctive pyroelectric substrate poly(vinylidene fluoride‐ co ‐hexafluropropylene (PVDF‐HFP), typical photothermal material carbon nanotube (CNT), and representative photocatalyst CdS. The transient photocurrent, electrochemical impedance spectroscopy, time‐resolved photoluminescence and pyroelectric potential characterizations indicate that the infrared‐light‐responsive carriers driver significantly promotes the photogenerated charge separation, accelerates carrier migration, and prolongs carrier lifetime. The photocatalytic hydrogen evolution efficiency is remarkably improved more than five times with the highest average apparent quantum yield of 16.9%. It may open up new horizons to photocatalytic technology for the more efficient use of infrared light. Abstract : Construction of a driver for photogenerated carriers: an infrared‐light‐activated pyroelectric field is introduced into photocatalysis, which functions as a carrier driver during the photocatalytic reaction, considerably promoting charge separation and prolonging the carrier lifetime. The photocatalytic hydrogen evolution efficiency is remarkably improved more than five times. The generation of the pyroelectric field and its effect on charge transfer behavior are investigated.